Dental Malocclusion Impact On Self-Esteem Levels Among Teenagers: Life Sciences -Dentistry - Vanka, Dr Amit; Sadaka Alsindi, Dr. Razan; Fouad Alyaqoub, Dr. Reyam; Ahmad Alsaidi, Dr. Esraa; Abdullah Aljizani, Dr. Fatimah; Abdullah Almaliki, Rasha; Hossain Abul Kasem, Fatima Mohammed; Wali, Dr Othman; Roby, Dr. Shiba; Vanka, Dr Shanthi (International Journal of Life Science and Pharma Research, 2023)
In recent years, there has been an upsurge in research on the quality of life-related to dental health since this indicator gaugesan individual’s sense of well-being. Orthodontic treatments have significantly helped improve oral health-related quality of life. The impactof malocclusion on quality of life is substantial, with low self-esteem. Teenagers, particularly those still developing, are often concernedabout their appearance and level of confidence. The study is aimed to determine the impact of dental malocclusion on self-esteem levelsamong teenagers attending a private dental college in Jeddah. A questionnaire was used to obtain the data. Nearly 75% of females and25% of males consider oral health an integral part of general health and visit the dentist regularly. 70.5% of females, compared to 29.5%of males, think they need orthodontic treatment. The females responded that straight teeth make them popular (66.3%) and successful(60.1%). The potential effects of dental malocclusion and its correction on adolescents’ general quality of life should also be considered.While orthodontic treatment can improve physical appearance and self-esteem, it may also cause discomfort, pain, and financial strain.Future research might explore the potential advantages and disadvantages of orthodontic treatment for adolescents to guide professionalpractice and patient decision-making better. Most female participants in the survey believed that orthodontic treatment was vital sincehaving straight teeth contributed to one’s success and popularity. To avoid being taunted about their teeth, the respondents believedthey needed to straighten them.